Os desafios e os efeitos da transferência no trabalho com adolescentes em cumprimento de medida socioeducativa em meio aberto e ameaçados de morte - Adriana Timóteo de Oliveira (2019)
This dissertation aims to present a reflection on challenges and effects of transference in the work with teenagers threatened with death in compliance with socio-educational measures in the open. The ignition point to the investigation was the follow up to the teenagers in the service to the socio-educational measures in the city of Counting, MG. It was picked excerpts of three clinical cases that turned it possible to identify the point showing the establishment of the transference, and, then, it was analyzed their effects under the teenager assumed position before the threat of death. It was also used the psychoanalytical theoretical framework to make the discussions, circumscribed within three main topics, that is, (1) adolescence, (2) risk and (3) transference. Our main hypothesis was that the psychoanalytical listening to the teenager, in the referred context, benefits the transference establishment, which can lead to its subjective implication. For its turn, from the implication in the risk context the teenager takes the chance to have a choice - for life or for death - and become responsible for it on his own. Their approach by speech as an effect of the transference provides a certain treatment to delight, and so it can awake in the teenager the desire for life.